Letramento estatístico: análise e reflexões sobre as tarefas contidas no material didático da Secretária Estadual de Educação de São Paulo para o ensino médio - Cobello, Lucas Soares (2018)
This dissertation is focused on statistical education in high school, in order to carry out the analysis of the tasks proposed in the material distributed by the State Department of Education of São Paulo, known as Teacher's Notebook and Student Notebook. This analysis had as educational product the elaboration of a teaching sequence based on these reflections and based on our theoretical references, these being the statistical literacy proposed by Iddo Gal, the registers of semiotic representation of Raymond Duval and the levels of comprehension and reading of graphs proposed by Frances R. Curcio. We tried to answer the following research question: what are the levels of literacy addressed in the learning situations of the Teacher's and Student's Notebook? For this we developed a qualitative documentary research. First, a bibliographical survey was carried out, with the objective of knowing the scenario of statistical education and its challenges, the analysis and reflection of the contents present in the curricular documents in force at national and state level were analyzed, the statistical literacy for secondary education . The investigation of the content of these tasks, pointed out that they present interesting themes to approach, such as the question of social inequality or the evaluation of the temperature of a region, however, the context treated is questionable in relation to the students' daily lives. Based on the problems found, a didactic sequence is presented that can guide the work of the teacher in the classroom, enabling the statistical literacy to be developed in its various elements of knowledge and disposition.